2017
DOI: 10.1097/txd.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab (Anti-IL-6R) Suppressed TNFα Production by Human Monocytes in an In Vitro Model of Anti-HLA Antibody-Induced Antibody-Dependent Cellular Cytotoxicity

Abstract: BackgroundWe previously demonstrated that natural killer (NK) cells activated via FcγRIIIa (CD16) interactions with anti-HLA antibodies binding to peripheral blood mononuclear cells (PBMCs) in the in vitro antibody-dependent cellular cytotoxicity (ADCC) assay produced IFNγ. Here we investigate if other CD16 bearing cells are responsive to alloantigen via alloantibody in the in vitro ADCC and if the ADCC-induced cytokine reactions and cytotoxicity can be modified by the anti-interleukin 6 receptor (IL-6R) monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…HLA class II binding has been associated with increased IL-6 production in endothelial cells and promotion of TH17 lymphocyte expansion 63 . In peripheral blood mononuclear cells isolated from transplant patients, some studies have shown HLA antibodies increase cytokines (TNF-α, IFN-γ, and IL-6 64 ) whereas others have not 65 . We found an association between IL-6 and HLA mismatch, but not HLA DSA.…”
Section: Discussionmentioning
confidence: 47%
“…HLA class II binding has been associated with increased IL-6 production in endothelial cells and promotion of TH17 lymphocyte expansion 63 . In peripheral blood mononuclear cells isolated from transplant patients, some studies have shown HLA antibodies increase cytokines (TNF-α, IFN-γ, and IL-6 64 ) whereas others have not 65 . We found an association between IL-6 and HLA mismatch, but not HLA DSA.…”
Section: Discussionmentioning
confidence: 47%
“…On the other hand, fingolimod (FTY720) increases NK cytotoxicity by up-regulation of NKp30, NKp44 and NKG2D expression (79). Furthermore, the new generation of anti-inflammatory biologicals such as tocilizumab (anti-IL6R) (80), anti-TNF drugs (81), B cell depleting monoclonal antibodies such as rituximab (82), or kinase inhibitors (83) can also influence NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Simulating such features in a preclinical drug screening tool would be transformative for the translational process necessary for optimizing rheumatological care. Here, we have developed a human MSC-derived OTM and described its capacity to create a RA-like phenotype, which replicated in part the immunomodulatory effect of well-known anti-rheumatic drugs such as adalimumab [ 30 , 31 ] and tocilizumab [ 32 , 33 ], but also the antineoplastic agent milatuzumab [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we provide first evidence that effects of immunomodulatory drug candidates can be demonstrated in our MSC-derived OTM on mRNA level ( Figure 7 ). We used adalimumab [ 30 , 31 ], tocilizumab [ 32 , 33 ] and milatuzumab [ 34 ] for proof of concept, as these are clinically used monoclonal antibodies directed against TNFα, IL-6 and MIF. Recent work has indicated that TNFα may mediate its angiogenic effect in RA via IL-8 and VEGF [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation